2005
DOI: 10.1128/jcm.43.5.2330-2338.2005
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Diversity inCampylobacter jejuni: Identification ofC. jejuni81-176-Specific Genes

Abstract: Since the publication of the complete genomic sequence of Campylobacter jejuni NCTC 11168 in February 2000, evidence has been compiling that suggests C. jejuni strains exhibit high genomic diversity. In order to investigate this diversity, the unique genomic DNA sequences from a nonsequenced Campylobacter strain, C. jejuni 81-176, were identified by comparison with C. jejuni NCTC 11168 by using a shotgun DNA microarray approach. Up to 63 kb of new chromosomal DNA sequences unique to this pathogen were obtained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
45
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(48 citation statements)
references
References 41 publications
2
45
1
Order By: Relevance
“…Given that gastroenteritis due to C. jejuni infections are hyperendemic among young children (< 5 years) in tropical resource-poor settings, it is expected that the prevalence of C. jejuni-induced GBS would be prevalent among individuals of < 5 years of age. Other researchers, using a broader case definition that includes all age groups for GBS surveillance, have published reports of bimodal distribution of GBS cases by age, with more cases identified in young adults (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) and the elderly (significantly higher) [4,16,29,30].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given that gastroenteritis due to C. jejuni infections are hyperendemic among young children (< 5 years) in tropical resource-poor settings, it is expected that the prevalence of C. jejuni-induced GBS would be prevalent among individuals of < 5 years of age. Other researchers, using a broader case definition that includes all age groups for GBS surveillance, have published reports of bimodal distribution of GBS cases by age, with more cases identified in young adults (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) and the elderly (significantly higher) [4,16,29,30].…”
Section: Discussionmentioning
confidence: 99%
“…The Penner heat-stable (HS) serotypes of C. jejuni strains that are attributed to GBS include serotype HS:19 which has been reported to occur globally; and serotype HS:41 which reportedly is restricted to Cape Town, South Africa [8,11,12,[18][19][20]. During a five year study period (January 2005 to December 2009) a total of 1 501 AFP cases were reported in South Africa, of which 67.2% (1009/1501) were children aged < 5 years of age and 54.3% (815/1501) were male [21].…”
Section: Introductionmentioning
confidence: 99%
“…Similar comparative genomic hybridization studies on Campylobacter jejuni (Dorrell et al 2001) and V. cholerae (Dziejman et al 2005) identified strain specificities in RM systems. The presence of genes encoding type-I RM systems correlated with different gastric responses of the host to Helicobacter pylori (Bjorkholm et al 2002), and it is thought to modulate the virulence potential of Campylobacter strains (Poly et al 2005). The identification of a worldwide distributed L. pneumophila strain, resembling strain Paris, now opens exciting possibilities of research to find out whether the specific genes contribute to improved interaction with the host or to improved fitness in the environment.…”
Section: Pneumophila Serogroup 1 Isolates Carry a Particular Lps Gmentioning
confidence: 99%
“…This suggests that genes necessary for induction of inflammatory diarrhea are among the genes shared by 81-176 and GC8486 and that the reasons for the higher level of in vitro invasion by 81-176 remain obscure (17). Collectively, multiple genome data indicate that the major genetic differences among C. jejuni strains are in the three carbohydrate loci (10,17,31,33,34), and it may be that differences in these surface antigens affect virulence both in vivo and in vitro. However, the possibility that more subtle changes in the nucleotide sequences of genes common to Campylobacter strains may also modulate pathogenesis cannot be ruled out.…”
Section: Vol 75 2007mentioning
confidence: 99%
“…The publication of the genome of a clinical isolate of C. jejuni from the United Kingdom, NCTC 11168 (31), elucidated much about the biology of this bacterium but revealed no novel virulence factors that it has in common with other bacteria other than a previously unrecognized capsular polysaccharide (31). Whole-genome microarrays have been used extensively to explore the genomic diversity of C. jejuni (9,21,22,30,(32)(33)(34)38), and recently the complete genomes of a second C. jejuni strain, RM1221, which was isolated from chicken skin but whose virulence properties are unknown, and strains of Campylobacter coli, Campylobacter lari, and Campylobacter upsaliensis have been published (10). Ten additional strains of Campylobacter spp.…”
mentioning
confidence: 99%